Organizing growth - Garicano, Luis 1967-; Rossi-Hansberg, Esteban (National Bureau of Economic Research, 2007)
We study the impact of information and communication technology on growth through its impact on organization and innovation. Agents accumulate knowledge through two activities: innovation (discovering new technologies) and exploitation (learning how to use the current technology). Exploitation requires the development of organizations to coordinate the work of experts, which takes time. The costs and benefits of such organizations depend on the cost of communicating and acquiring information. We find that while advances in information technology that lower information acquisition costs always increase growth, improvements in communication technology may lead to lower growth and even to stagnation, as the payoff to exploiting innovations through organizations increases relative to the payoff of new radical innovations.